THE CORRELATION BETWEEN STUDENTS’ SYNTAX SCORES AND STUDENTS’ WRITING SCORES - Sari, Indah Purnama; Wijaya, Bambang; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak: Tujuan penelitian ini adalah untuk meneliti hubungan antara nilai syntax dengan nilai menulis siswa semester lima program studi pendidikan Bahasa Inggris, program regular B, Fakultas Keguruan dan Ilmu Pendidikan tahun akademik 2013/2014. Untuk mencapai tujuan ini, peneliti menggunakan studi korelasi sebagai metode penelitiannya. Populasi penelitian ini adalah siswa semester lima program studi pendidikan Bahasa Inggris, regular B, kelas A dan kelas B, yang terdiri dari 50 siswa. Sampel penelitian ini diambil dari kedua kelas A dan kelas B, terdiri dari 50 siswa. Data penelitian dikumpulkan menggunakan teknik dokumentari. Hasil penelitian menunjukkan bahwa tidak ada korelasi antara nilai syntax dan nilai menulis siswa. Hal ini berdasarkan penghitungan nilai koefisien korelasi Pearson r sebesar 0.236. Berdasarkan nilai tersebut, peneliti menyimpulkan bahwa Null hypothesis diterima dan Alternative hypothesis ditolak.   Kata kunci: Korelasi, Nilai Syntax, Nilai Menulis Abstract: The purpose of this research is to investigate the correlation between the students’ syntax scores and students’ writing scores of the fifth semester students of English education study program, regular B Program, Teacher Training and Education Faculty of Tanjungpura University in academic year 2013/2014. To achieve this goal, the researcher used correlational study as the method of this research. The population of this research was class A and class B of the fifth semester students of English education study program, regular B, that consist of 50 students. The sample of this research was taken from both class A and class B, consist of 50 students. The data of this research were collected by using documentary technique. The finding of this research showed that there is no correlation between students’ syntax scores and students’ writing scores. It is based on the calculation score of Pearson r correlation coefficient that is 0.236. Based on the score, the reseacher concluded that the Null hypothesis was accepted and Alternative hypothesis was rejected.   Keywords: Corelation, Syntax Scores, Writing Scores